Downregulation of LHPP Expression Associated with AFP Acts as a Good Prognostic Factor in Human Hepatocellular Carcinoma. (27th August 2021) - Chao, Xu; Zhang, Wei; Wu, Jieqiong; Feng, Xuesong; Shi, Hailong; Zhao, Luyan; Shen, Haiyu; Jiang, Chao
Abstract : Background. Phospholysine phosphohistidine inorganic pyrophosphate phosphatase (LHPP) serves as a tumor suppressor in hepatocellular carcinoma (HCC), but the correlation between the expression of LHPP and the clinical parameters of oncogenic progression is still not well defined. This study is to reveal the correlation between the expression of LHPP in HCC and their clinical parameters. Methods. Immunohistochemical analysis was used to assess the correlation between the expression of LHPP and the clinical parameters of HCC. Expressions of LHPP in HCC tissues and cultured HCC cells were detected by Western blot and quantitative real-time polymerase chain reaction (qRT-PCR). LHPP, gamma-glutamyl transferase (GGT), and α -fetoprotein (AFP) expression levels in blood or HCC tissues were detected by enzyme-linked immunosorbent assay (ELISA). The Spearman rank correlation coefficient was used to evaluate the correlation of the expression of LHPP and the clinical index of HCC. Correlation of survival and expression of LHPP were analyzed using the Kaplan-Meier method and the log-rank test. Results. Expressions of LHPP in HCC tissues were significantly downregulated than their paired adjacent normal tissues. A significant positive correlation was found between the cytoplasm and nuclear expression of LHPP in both HCC and their paired adjacent normal tissues. The expression of LHPP negatively correlated with the levels of GGT in the cytoplasm of adjacent tissues and with the AFP level in the nucleus of HCC cells. Relative levels of LHPP in HCC tissues were markedly lower than those of the paired adjacent normal tissues. Relative levels of LHPP in LO-2 cells were higher than those of HepG2, BEL-7404, and SMMC-7721 cell lines. The overall survival and DSF survival of patients with the high expression of LHPP were much higher than those with the low expression of LHPP in paired adjacent normal tissue. Conclusions. LHPP is associated with the AFP level and acts as a good prognostic factor in HCC.